VOLTAGE SENSORLESS CONTROL OF FIVE-LEVEL PACKED U-CELL INVERTER BASED ON LYAPUNOV APPROACH FOR GRID-CONNECTED PHOTOVOLTAIC SYSTEM (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper deals with the nonlinear control of a five-level packed U-Cell (PUC5) inverter used in a grid-on photovoltaic (PV) system. The sensorless modulation strategy is adopted to control the switching of the six power switches. This topology generates a five-level output voltage with fewer active and passive components than traditional multilevel inverters. A nonlinear controller was designed to control the grid current using the Lyapunov theorem to ensure the asymptotic stability of the overall system. The proposed control scheme addresses two key challenges: minimizing the injected grid current's total harmonic distortion (THD) while balancing the capacitor voltage at their reference under various operating conditions. The efficiency of the proposed approach was comprehensively evaluated using theoretical analysis, mathematical modeling, and simulation results obtained using MATLAB/Simulink software.
Keywords: Packed U-cell; Multilevel converter; Lyapunov control theory